Comparative Study of Marital Rape as A Reason for Divorce In Indonesia, Malaysia and Singapore - Astuti Vitria Utami Ningsih; Syaiffudin Zuhdi (Proceeding International Conference Restructuring and Transforming Law, 2023)
Marital is an act of violence or coercion by a husband/wife against a partner who is obliged to engage in sexual activity in marriage regardless of the partner's status sexual intercourse that is carried out vaginally, orally or anally by force, given threats or is carried out while in an unconscious state . The research method used is normative legal research. In Indonesia, marital rape itself is included in the realm of domestic violence which is regulated in Law No. 23 of 2004, while in Malaysia and Singapore there are no specific laws governing marital rape. But a wife who is in the process of divorce can ask for protection.